TAJIKISTAN ENERGY SECTOR: PRESENT AND NEAR FUTURE - VALAMAT-ZADE, Timur (CENTRAL ASIA AND THE CAUCASUS, 2008)
Economically efficient use of energy is a major indicator which largely determines the economic development level of any country, its national security, and the well-being of its people. Sustainable economic progress in modern societies implies that the energy factor is a key component of this progress. In the final years of the U.S.S.R., Tajikistan’s electric power industry based on hydropower was one of the best not only among the Union republics, but also among Asian countries. Past political events have had an adverse effect on the republic’s energy sector, but nevertheless, in contrast to many other sectors, it has passed this test and is now in the initial stage of recovery. Let us consider the current state of the republic’s electric power potential and its position compared to some CIS countries. Tajikistan generates four times more electricity than Moldova, three times more than Armenia, over twice as much as Georgia, a third more than Turkmenistan, and more than Kyrgyzstan. Nevertheless, there is an acute shortage of electricity in the republic. In winter, the population suffers and enterprises (including emerging businesses) incur losses, and this significantly hinders entrepreneurial activity in the country. In the conditions of tight restrictions on electricity consumption (limits), many enterprises suffer such heavy losses as to go out of business. As it happens, hydroelectricity is the backbone of Tajikistan’s energy sector. In this area, nature has endowed the republic with a huge po tential. Its renewable and environmentally clean water resources hold promise of a bright future for Tajikistan. The country’s 14,500 glaciers (with a total area of 11,000 sq km, or about 8% of its entire territory) give rise to all large rivers whose waters are used in the national economy. Tajikistan has 947 rivers over 10 km long, with a total length of 28,000 km. Overall, there are more than 25,000 rivers and streams, totaling about 90,000 km in length. Average drainage density in the country is close to 0.6 km per sq km. Rivers are mostly fed by seasonal snowmelt runoff, whose share of annual river flow is 75- 80%; the share of glacial runoff is 15-20%, and that of rainfall runoff, close to 5%. Average annual flow in Tajikistan is 76.7 cu km (1990), including 22.1 cu km of transboundary inflow from the territory of neighboring countries and 54.6 cu km of internally generated river flow. The republic’s lakes hold 46.3 cu km of water. In view of the above, Tajikistan ranks first in Central Asia and eighth in the world in terms of hydropower resources, which exceed 527 billion kWh per year. In terms of potential hydropower resources per square kilometer (3,682.7 thousand kWh per sq km per year), the country ranks first in the world, far surpassing other states. Unfortunately, only 3.1% of these resources are currently being used, mostly by hydroelectric power plants (HPPs) built on the Vakhsh River. Total installed HPP capacity in Tajikistan is 4,070 MW. The energy system also includes two thermal plants with a total capacity of 318 MW. Average annual electricity production, depending on the dryness of the year and the availability of fuel at thermal plants, is about 16.5 billion kWh. Tajikistan’s largest hydropower station, the Nurek HPP on the Vakhsh River, has nine generating units with a total capacity of 3,000 MW and average annual output of more than 11.2 billion kWh. Downstream lies the Baipaza HPP (600 MW, 2.5 billion kWh), followed by a system of smaller hydropower stations: Golovnaya (240 MW), Perepadnaya (29.5 MW) and Central (15.1 MW). Under the project, the Vakhsh hydropower system should include nine HPPs with a total capacity of 9,195 MW, five of which are already in operation.